2019
DOI: 10.1515/jisys-2019-0106
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Twitter Sentiment Analysis Using Hybrid Approach and by Accounting Local Contextual Semantic

Abstract: Abstract This paper addresses the problem of Twitter sentiment analysis through a hybrid approach in which SentiWordNet (SWN)-based feature vector acts as input to the classification model Support Vector Machine. Our main focus is to handle lexical modifier negation during SWN score calculation for the improvement of classification performance. Thus, we present naive and novel shift approach in which negation acts as both sentiment-bearing word and modifier, and then we shift t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…The lexicon-based approach, on the other hand, requires manual input of sentiment lexicons and performs well in any domain but fails to encompass complete informal lexicons. The hybrid approach will help to overcome the limitations of both approaches, thus enhancing performance, efficiency, and scalability [ 22 , 23 ]. Research has shown that using a hybrid approach not only accelerates accuracy and maintains stability but also provides better results than using one approach or one standard tool [ 23 , 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…The lexicon-based approach, on the other hand, requires manual input of sentiment lexicons and performs well in any domain but fails to encompass complete informal lexicons. The hybrid approach will help to overcome the limitations of both approaches, thus enhancing performance, efficiency, and scalability [ 22 , 23 ]. Research has shown that using a hybrid approach not only accelerates accuracy and maintains stability but also provides better results than using one approach or one standard tool [ 23 , 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…Nonetheless, critics such as Farooq et al (2017) and Gupta & Joshi (2019) have argued that the aforementioned methods might work well for simple text, but will fail in the case of compound and complex text (having more than one clause or conjunctions), owing to the presence of conjunction such as "but," which may limit the negation scope to only a single clause. As such, the scope of negation may possibly end before a static window termination or before the occurrence of the first punctuation mark.…”
Section: Negation Scope Resolutionmentioning
confidence: 99%
“…Thus, token "failure_NEG" would be extracted during feature engineering instead of "failure". http://journals.uob.edu.bh Furthermore, we exclude few negation tweets from the scope determination procedure which are having explicit negation words but literally, there is no sense of negation [15] as in tweet:…”
Section: Negation Modellingmentioning
confidence: 99%